PENGELOLAAN KEUANGAN (FINANCIAL MANAGEMENT) BERDASARKAN ANALISIS STANDAR AKUNTANSI KEUANGAN ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK ETAP): (STUDI KASUS PADA KOPI SUWAY LAMPUNG) - Istiqamah, Indah; Destalia, Mediya (Jurnal Kompetitif Bisnis, 2023)
This study aims to find out descriptive findings regarding financial management, especially cash flow at Kopi Suway Lampung based on an analysis of the application of financial reports in accordance with the Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP). Data collection methods used in this study wereinterviews, observation and documentation. The results of the study show that Kopi Suway has not carried out financial management on cash flow and Kopi Suway has also not prepared financial reports in accordance with SAK ETAP. The obstacle faced in the preparation of financial reports is the lack of human resources owned by Kopi Suway and the lack of a clear division of labor, especially in specific financial records. In addition, Kopi Suway has not yet digitized the financial recording process. In Kopi Suway's operational activities, it has no debts and receivables, so what can be done is to reduce the inventory age to increase cash flow. This also aims to obtain optimal income and in accordance with the targets set by the owner of Kopi Suway.